LORAWAN GATEWAY PLANNING USING AS923-2 FREQUENCY IN TASIKMALAYA FOR MONITORING ODC - Enriko, I Ketut Agung; Nizar Gustiyana, Fikri; Chandrayana Giri, Gede (Jurnal Teknik Informatika (Jutif), 2023)
This study aims to design a LoRaWAN network and find out how many gateways are needed to cover the research area and to design an IoT-based monitoring system for ODC devices on the FTTH network based on data at PT. Telkom Witel Tasikmalaya. The method used is a simulation using Atoll software version 3.40 and several calculation stages to predict the parameters of RSSI (Received Signal Strength Indicator) and SINR (Signal to Interference Noise Ratio) in a planning area of ​​358.66 km2. This study using AS923 frequency with a bandwidth of 125 kHz and a Spreading factor of 10. The results obtained are signal strength (RSSI) and signal quality (SINR) parameters. Based on the results of calculations and planning simulations, it produces 20 gateways using SF 10 with an RSSI parameter of -69.53 dBm and a SINR parameter of 20.21 dBm, each gateway can cover 4-5 km2 in the planning area.